Hedonism in the Student Environment in the Era of Globalization - Naufal Adib Putra; Shelly Adisti Setiawati; Maria Adelweys Niken Aprilia Sinaga; Richie Lay Tan; Reva Naira (IJRAEL: International Journal of Religion Education and Law, 2022)
This study aims to determine the hedonistic lifestyle found in the student environment in the era of globalization. Hedonism is a human behavior that makes material pleasure and enjoyment a priority in life. Social media is one of the factors that triggers the growth of hedonism in society. Through social media, people can easily absorb inspiration or offers that can attract people's attention to buy these goods. Without realizing it, this can lead to hedonism in society, especially students, because they can buy things that they want, not their needs. In the era of modernization, many students are hedonistic, because they actually have a high level of contentment. The sense of prestige that exists, can also influence a person to be hedonic. students will compete to build their confidence again by buying things according to their wishes. The research method used is a qualitative approach. The sample in this study are 20 students at Tarumanagara University. Data collection techniques were carried out by distributing open questionnaires online using google form. The results of this study illustrate that hedonism grows and develops in student life. Someone who is hedonic generally has a selfish, consumptive personality, and does not have careful planning in his life. So, in this era of globalization, students must be able to make restrictions on themselves, so they are not easily entangled in a lifestyle or hedonistic nature that only gives false pleasure.